Stress management, leukocyte transcriptional changes and breast cancer recurrence in a randomized trial: An exploratory analysis. (December 2016) - Antoni, Michael H.; Bouchard, Laura C.; Jacobs, Jamie M.; Lechner, Suzanne C.; Jutagir, Devika R.; Gudenkauf, Lisa M.; Carver, Charles S.; Lutgendorf, Susan; Cole, Steven W.; Lippman, Marc; Blomberg, Bonnie B.
Highlights: Conserved transcriptional response to adversity (CTRA) rises with cancer treatment. Cognitive behavioral stress management (CBSM) buffers CTRA during treatment. Less CTRA rise during cancer treatment predicts longer 11-yr disease-free survival. CBSM modulates disease relevant biobehavioral processes in breast cancer treatment. Abstract: Purpose: Cognitive behavioral stress management (CBSM) is an empirically-validated group-based psychosocial intervention. CBSM is related to decreased self-reported indicators of psychological adversity during breast cancer treatment and greater disease-free survival (DFS) vs. a control condition. This study examined relationships between CBSM, DFS, and a potential biobehavioral pathway linking these variables in breast cancer patients through a gene expression composite representing the leukocyte conserved transcriptional response to adversity (CTRA). Design: Women with stage 0-IIIb breast cancer completed questionnaires and provided blood samples post-surgery. Participants were randomized to 10-week group-based CBSM or a psychoeducation control group and followed at 6 months, 12 months, and median 11 years. In total, 51 participants provided blood data for longitudinal analyses (CBSM n = 28; Control n = 23). Mixed model analyses examined CBSM effects on 6–12 month changes in CTRA expression (53 indicator genes representing pro-inflammatory, anti-viral and antibody production signaling). Cox regression models assessed the relationship between 6 and 12 month changes in CTRA expression and 11-year DFS. Results: Patients randomized to CBSM showed attenuated 6–12 month change in CTRA gene expression, whereas patients randomized to control showed increased CTRA expression ( p = 0.014). Average DFS was 5.92 years ( SD = 3.90). Greater 6–12 month CTRA increases predicted shorter 11-year DFS controlling for covariates ( p = 0.007). Conclusions: CBSM attenuated CTRA gene expression during the initial year of breast cancer treatment. In turn, greater increases in CTRA gene expression predicted shorter long-term DFS. These findings identify a biobehavioral oncology pathway to examine in future work.